The Development Of Rectangular Waveguide Bandpass Filter - Ahmad, Badrul Hisham; Shairi, Noor Azwan; Abdul Manap, Redzuan (2010)
The design and development of rectangular waveguide bandpass filter is presented in this paper. The principle of operation of the filter is that the posts act as shunt inductive discontinuities and the sections of the waveguide between the posts are half waveguide resonators. The bandpass operated at X band frequencies with 1 GHz bandwidth. Pass band is from 8 GHz to 9 GHz. Insertion loss achieved is less than 0.3 dB and return loss of more than 15 dB. Lower cut off frequency at 8 GHz is more selective than the upper cut off frequency at 10.5 GHz, which is 40dB and 20dB respectively. 3D simulator was used to model the structure and simulation results showed very good response.